Characterization of xylazine metabolism in rat liver microsomes using liquid chromatography–hybrid triple quadrupole–linear ion trap–mass spectrometry. (28th February 2013) - Lavoie, David St‐Germain; Pailleux, Floriane; Vachon, Pascal; Beaudry, Francis
Abstract : ABSTRACT: Xylazine is an α 2 ‐adrenoceptor agonist and it is widely used in veterinary anesthesia in combination with ketamine. There is limited information on the metabolism of xylazine. A quantitative method for the determination of xylazine by HPLC‐ESI/MS/MS was developed. The method consisted of a protein precipitation extraction followed by analysis using liquid chromatography electrospray tandem mass spectrometry. The chromatographic separation was achieved using a Thermo Betasil Phenyl 100 × 2 mm column combined with an isocratic mobile phase composed of acetonitrile, methanol, water and formic acid (60:20:20:0.4) at a flow rate of 300 μL/min. The mass spectrometer was operating in selected reaction monitoring mode and the analytical range was set at 0.05–50 μm . The precision (%CV) and accuracy (%NOM) observed were 2.3–7.2 and 88.2–96.4%. In vitro metabolism studies were performed in rat liver microsomes and results showed moderate cytochrome P450 affinity ( K m = 10.1 μm ) and a low metabolic stability of xylazine with a half‐life of 4.1 min in rat liver microsomes. Five phase 1 metabolites were observed. The main metabolite observed was an oxidation of the thiazine moiety at m / z 235 and, to a lesser extent, we observed the formation of N ‐(2, 6‐dimethylphenyl)thiourea at m / z 181 and three distinctive hydroxylated metabolites at m / z 237. Further experiments with ketamine and ketoconazole strongly supported that the metabolism of xylazine to its main metabolite is mediated by CYP3A in rat liver microsomes. Copyright © 2013 John Wiley & Sons, Ltd.